An Analysis of Visually Impaired Students' Ability to Understand Arabic Lessons at Muhammadiyah 1 Senior High School Ponorogo - Mukaromah, Muhimmatul; Fitiya, Hasni (Naatiq: Journal of Arabic Education, 2025)
This study aims to determine: 1) The ability of visually impaired students to master the Arabic language at Muhammadiyah 1 Senior High School Ponorogo. 2) The factors affecting the ability of visually impaired students to understand Arabic learning at Muhammadiyah 1 Senior High School Ponorogo. 3) The learning models used for visually impaired students at Muhammadiyah 1 Senior High School Ponorogo. The results of this study indicate that the ability of visually impaired students to learn Arabic at Muhammadiyah 1 Senior High School Ponorogo is as follows: 1) The ability of visually impaired students to understand Arabic learning is considered quite good, where students can follow the learning process without falling behind regular students. 2) The factors affecting the ability of visually impaired students to understand Arabic learning at Muhammadiyah 1 Senior High School Ponorogo include internal and external factors. Internal factors include learning attitude, learning motivation, focus in learning, self-confidence, and study habits. External factors include family, the school environment, including teachers, peers, and available facilities to support the continuity of the learning process. 3) Teachers at Muhammadiyah 1 Senior High School Ponorogo use a direct teaching model because this approach allows teachers to quickly enhance students' knowledge and confidence. This direct teaching model focuses on the way teachers actively engage in classroom activities, making it highly suitable for visually impaired students who have visual limitations. In addition, a cooperative learning model is also applied at Muhammadiyah 1 Senior High School Ponorogo, which trains students to collaborate with their groups.